(untitled) (One Health & Risk Management, 2021)
Introduction. Chemicals are present in the national economy and bring benefits on which modern society is completely dependent, but they can also present risks if they are not correctly managed. Recently, in the world, the chemicals have significantly increased in use, especially household products used in daily life, which poses a potential risk to public health, caused by their irrational use. An important aspect in the prevention of acute non-professional chemical poisonings (ANPCP) is the awareness of the population about the dangers of inappropriate use of chemicals and the diseases they can generate. Material and methods. A descriptive and retrospective study was performed. Data from the Statistical Form f. 50-san "Statistical report on health promotion and health education", f. 18-san. "Statistical report on state surveillance and control of public health in the district, municipality", Model report on the organization of the National Week for combating of acute non-professional chemical poisonings were analysed. Results. Statistical data analysis showed that, since 2013, the Republic of Moldova, together with several states, have organized International Campaigns to prevent lead poisoning. At the same time, since 2018, was carried out National Prevention Week of acute non-professional chemical poisonings by public health specialists, Ministry of Health, Labour and Social Protection (MHLSP), territorial medical institutions together with specialists of the Ministry of Education, Culture and Research. In 2021, according to the joint Order of MHLSP and the National Agency for Food Safety no. 237/127 of 19.03.2021, for the first time was organized the National Health Promotion Week through the rational application of phytosanitary products. Several events (seminars, public lessons, round tables) were organized during this week, aimed at public informing and raising awareness on the health effects of chemicals exposure, by increasing the level of knowledge and raising society’s awareness on avoidance of using toxic chemicals, especially veterinary drugs in treatment of humans. Thus, more than 2,000 people were informed and trained on how to properly handle and store chemicals, as well as on measures to prevent chemical poisonings etc. The assessed statistical data established that, in the country, a total of 30,323 cases of ANPCP were registered during 2012-2020, including 912 deaths. Most cases occurred in 2013, of which 6292 were affected and 219 led to death. Since 2014, it can be noted a decreasing trend of cases, when were reported 5619 poisonings, reaching 2145 cases in 2018 and 1494 cases in 2020. Conclusions. The organization of Health Promotion Weeks in chemical risks field, of has a positive impact on population health, with a decrease in the level of morbidity associated with chemicals products. The cases of acute non-occupational chemical poisonings has decreased from 6292 cases in 2013 to 1494 cases in 2020. With the aim to improve the situation in this field and increase the level of knowledge of the citizens, it is necessary to continue the health promotion measures in this field.